Addressing the complexity of spatial teaching: a narrative review of barriers and enablers - Bufasi, Ergi; Lin, Ting Jun; Benedicic, Ursa; Westerhof, Marten; Mishra, Rohit; Namsone, Dace; Dudareva, Inese; Sorby, Sheryl; Gumaelius, Lena; Klapwijk, Remke M.; Spandaw, Jeroen; Bowe, Brian; et al. (Frontiers in Education, 2024)
Extensive research has established that spatial ability is a crucial factor for achieving success in Science, Technology, Engineering, and Mathematics (STEM). However, challenges that educators encounter while teaching spatial skills remain uncertain. The purpose of this study is to develop a research framework that examines the interrelationships, barriers, and enablers amongst various educational components, including schools, teachers, students, classrooms, and training programs, that are encountered when teaching for spatial ability development. A comprehensive analysis of relevant literature, in combination with an in-depth examination of the primary science and mathematics curricula of Ireland, Latvia, Sweden, and the Netherlands, is conducted to gain a more focused understanding of the inclusion of spatial components in the curriculum. A thorough examination of international research, in combination with a detailed review of the primary sScience and mMathematics curricula in Ireland, Latvia, Sweden, and the Netherlands, is undertaken to acquire a more concentrated comprehension of the incorporation of spatial components in the curriculum. The study review seeks to establish the fundamental factors that enable or hinder teachers in terms of curriculum, pedagogy, pedagogical content knowledge, and spatialized classroom practices.